Unraveling the role of HIF2α in melanoma progression and epithelial–mesenchymal transition - Zhao Han; Yanling Gao; Zhifeng Li; Zhao Liu; Jianzhong Zhang; Tingting Jing; Yanyan Xv; Guoying Miao; Xiaojing Li; Aijun Chen (Scientific Reports)
Abstract Melanoma is a highly heterogeneous and aggressive malignancy. Hypoxia within the tumor microenvironment is closely associated with tumor progression. However, the role of hypoxia-inducible factor 2α (HIF2α), a key transcription factor, in melanoma remains poorly understood. In this study, transcriptome analysis compared HIF2α expression between melanoma patient and control samples. Single-cell RNA sequencing categorized cells into high- and low-HIF2α expression groups. Ligand–receptor interactions (CellChat), enrichment analysis (GSEA/GSVA), immune regulatory network, and metabolic pathway analyses were performed. The correlation between HIF2α and genes involved in hypoxia, autophagy, and epithelial–mesenchymal transition (EMT) was explored, alongside its relationship with clinical stage. Experimentally, A375 cells were cultured under normoxic and hypoxic conditions, transfected with ShRNA-NC or ShRNA-HIF2α, and mRNA levels of HIF2α, E-cadherin, N-cadherin, and Vimentin were quantified using real-time PCR. Differential expression analysis showed significant upregulation of HIF2α in melanoma samples. Ligand–receptor interaction analysis emphasized its role in modulating the tumor microenvironment. Enrichment analyses (GSEA/GSVA) revealed HIF2α involvement in key oncogenic pathways. Correlation analysis linked HIF2α to genes related to hypoxia, autophagy, and EMT, and its expression was associated with advanced clinical stages. In vitro, hypoxia increased HIF-2α, N-cadherin, and Vimentin mRNA levels, while decreasing E-cadherin. HIF-2α knockdown reversed these effects, promoting E-cadherin and suppressing N-cadherin and Vimentin under hypoxia. This study underscores the critical role of HIF2α in melanoma progression, suggesting its involvement in regulating the tumor microenvironment and associated metabolic pathways. As a potential biomarker and therapeutic target, HIF2α offers new insights into the clinical management and treatment of melanoma.